Invitation: contexts, culture et communication - jarvis, Gilbert A. (Fort Worth : Holt, Rinehart and Winston, 1988)
English and French Revised edition of Invitation: French for communication and cultural awareness / Gilbert A. Jarvis ...=et. al= 2nd edition
Keywords: french language -- text books for foreign speakers -- English; Frenchlanguage -- grammar -- 1950